Tahlilul Akhto' al-Imla'iyyah wal Khotiyyah fil Kitabah al-Arobiyyah li Tholabah Roudhotut Ta'lim Al-Qur'an Nurul Huda Bi Kedungkandang Malang - Maulana, Agus; Sunarko, Asep; Anis, Muhammad Yunus; Hakiki, Dava Riski Muftia; Rois, Ahmad (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
One type of language deviation can be language errors themselves. Language errors, especially in the realm of writing, often occur, especially among students who learn to write using Arabic. This research attempts to explore errors in writing Arabic in TPQ Nurul Hudaa Kedung Hutch, Malang City. This research is a hungry study with a qualitative descriptive approach using observation and interview methods to obtain the required data regarding errors in writing Arabic for students, then analyzed using data triangulation using induction thinking to reveal in depth the data that has been processed. Research at TPQ Nurul Huda Kedungdang Malang resulted in the conclusion that there are still many errors found in Arabic writing for students, especially in letters that are almost the same in writing or almost the same in pronunciation even though the writing form is different. This indicates that there is a need to increase students' understanding of letters that have similarities in both writing and pronunciation